Effect of Different Ecbolic Agents on Postpartum Reproductive Performance in Surti Buffaloes - Bhoi, Dhiren B.; Chaudhari, Naresh F.; Raval, Jitendra K.; Pandya, Gaurav M. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The study was conducted to evaluate the effect of different ecbolic therapies on puerperium in twenty four Surti buffaloes divided  into four different groups consisting of six animals in each. Buffaloes in Group-I (T1) were not given any treatment and considered as control group. Group-II (T2) and Group- III (T3) buffaloes were injected methylergometrine (5 mg) and dinoprost tromethamine (25  mg) i/m, respectively, immediately after parturition. The animals in Group-IV (T4) received oral herbal ecbolic, 100 mL, daily for first  10 days postpartum. The time required for placental expulsion, persistence of lochial discharge, involution of uterus and service  period were significantly (P
Keywords: Ecbolics; Postpartum fertility; Puerperial period; Surti buffalo